Applications of Nanobiotechnology - Stoytcheva, Margarita; Zlatev, Roumen (IntechOpen, 2020)
This book is dedicated to the applications of nanobiotechnology, i.e. the way that nanotechnology is used to create devices to study biological systems and phenomena. It includes seven chapters, organized in two sections. The first section (Chapters 1-5) covers a large spectrum of issues associated with nanoparticle synthesis, nanoparticle toxicity, and the role of nanotechnology in drug delivery, tissue engineering, agriculture, and biosensing. The second section (Chapters 6 and 7) is devoted to the properties of nanofluids and the medical and biological applications of computational fluid dymanics modeling.